2009
DOI: 10.1080/00016480802252243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of semicircular canal electrode implantation on hearing in chinchillas

Abstract: Conclusion-Implantation of vestibular prosthesis electrodes in chinchilla semicircular canal ampullae can be accomplished without significant loss of cochlear function; however, the risk of hearing loss with the current surgical technique is high.Objectives-To determine if it is possible to implant vestibular prosthesis electrodes into the labyrinth without damaging hearing, and to quantify the extent of hearing loss due to implantation.Method-The left semicircular canals of 6 chinchillas were implanted with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…In contrast, the intralabyrinthine approach might allow better selectivity of the stimulation but the risk of inducing hearing loss in this case is still unclear. Results of animal studies are controversial: some demonstrate that intralabyrinthine electrode insertion with or without electrical stimulation impairs hearing in most of the cases [60,61,62], while others show that it is possible to preserve auditory and vestibular function [63]. The results in human patients are not very encouraging in this respect.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, the intralabyrinthine approach might allow better selectivity of the stimulation but the risk of inducing hearing loss in this case is still unclear. Results of animal studies are controversial: some demonstrate that intralabyrinthine electrode insertion with or without electrical stimulation impairs hearing in most of the cases [60,61,62], while others show that it is possible to preserve auditory and vestibular function [63]. The results in human patients are not very encouraging in this respect.…”
Section: Discussionmentioning
confidence: 76%
“…We therefore studied the use of DC modulation in application to prosthetic stimulation of the vestibular nerve, an application with which we have significant experience [2136] and for which SCDS1’s ability to inhibit spontaneous activity would be especially advantageous.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas cochlear implant electrode arrays can be inserted near the auditory nerve while remaining completely in the scala tympani, implantation of electrodes near the semicircular canals’ cristae probably disrupts the membranous labyrinth. In a previous study of hearing in chinchillas undergoing vestibular electrode implantation, we found that hearing was compromised in 4 of 6 animals [12]; however, differences in size and surgical approach preclude generalization of these data to humans with certainty.…”
Section: Effects Of Vestibular Prosthesis Electrode Implantationmentioning
confidence: 96%